Structural Analysis of Humic Acid in Soil at Different Corn Straw Returning Modes through Fluorescence Spectroscopy and Infrared Spectroscopy - JinFeng Gao; Sen Dou; ZhiGuo Wang (International Journal of Analytical Chemistry)
The purpose of this study is to analyze the effects of different straw returning modes on the structure of humic acid (HA) in soil by fluorescence spectroscopy and infrared (IR) spectroscopy. Four different straw returning modes, including straw returning to topsoil (St), straw returning to subsoil (Ss), straw mixing with topsoil (Smt), and straw mixing with subsoil (Sms), were used in this study; the soil HA was analyzed after 12 months of corn straw returning by a combination of fluorescence spectroscopy and IR spectroscopy. Based on the results, it was established that IR spectroscopy can estimate the complication and oxidation degree of soil HA and also evaluate its aliphaticity and aromaticity. Monodimensional fluorescence spectroscopy could preliminarily determine the changes in the humification of HA through the fluorescence intensities. The intensity ratio of I456/I380 calculated from synchronous-scan fluorescence spectra could be used to evaluate the humification degree of soil HA. The total luminescence spectra of HAs provided more information on the fluorophores in the structure, including the amount and peak position of lignin-like structures and phenol-like or naphthol-like structures. Among the four straw returning modes, Ss is the most beneficial for reducing the oxidation degree and increasing the aromatization and humification degree of subsoil HA. It is believed that fluorescence spectroscopy and IR spectroscopy are relatively simple and sensitive methods for analyzing soil HA.